Psychometric Testing of the Chinese Version of the Coping and Adaptation Processing Scale-Short Form in Adults With Chronic Illness - Wang, Xiyi; Tang, Leiwen; Howell, Doris; Shao, Jing; Qiu, Ruolin; Zhang, Qi; Ye, Zhihong (Frontiers in Psychology, 2020)
Background: Adaptive capacity may serve as an indicator of the individuals’ coping behaviors towards illness management and may contribute to day-to-day living with chronic illness and improved quality of life. Practical and well-constructed instruments for measuring adaptation have not been adequately explored. An English 15-item Coping and Adaptation Processing-Short Form (CAPS-SF) for assessing adaptation has been created and validated in line with the underlying tenets of Coping and Adaptation Processing theory, but there is no applicable Chinese version. Methods: The CAPS-SF was translated and culturally adapted into simplified Chinese. Among Chinese adults with chronic illness, eighty-one patients were selected for cultural adaptation and 288 patients were approached for psychometric testing. Content validity was evaluated by an expert panel. Construct validity was tested by confirmatory factor analysis. Concurrent validity and predictive validity were analyzed by Spearman correlation coefficient. Reliability was assessed by internal consistency and test-retest coefficients. Floor/ceiling effect was calculated. Results: Adequate content validity was ensured by the expert panel. A four-factor structure (resourceful and focused, self-initiated and knowing-based, physical and fixed, and positive and systematic) describing individuals’ coping strategies was identified and verified. Concurrent validity and predictive validity were demonstrated by strong correlations with the confrontation of coping mode (r= 0.46) and a quality of life measure (r= 0.58). The McDonald’s Omega coefficient of total scale was 0.82. Split-Half reliability and test-retest reliability were 0.87 and 0.87. No floor/ ceiling effect was present. Conclusions: The Chinese version CAPS-SF is a theoretically based and culturally acceptable instrument with sound psychometric properties. Further studies are advocated to refine its four-factor structure.